Heterogeneity in Manufacturing Growth Risk - Daan Opschoor; Dick van Dijk; Philip Hans Franses (Tinbergen Institute, 2021)
We analyze output growth risk with respect to financial conditions across U.S. manufacturing industries. Using a multi-level quantile regression approach, we find strong heterogeneity in growth risk, particularly between the more vulnerable durable goods sector and the more resilient nondurable goods sector. Moreover, we show that industry characteristics significantly explain these differences. Large, or material intensive durable goods producing, or energy intensive nondurable goods producing industries are more vulnerable to adverse financial conditions, while industries engaging in labor hoarding, or with a high capital or overhead labor intensity are less susceptible.
Keywords: C21; E32; E44; L16; L60; 330; downside risk; business cycle; quantile regression; manufacturing; financial conditions